Counter-Terrorism Strategies in Pakistan: Addressing the Menace of Terrorism - Mali, Ghulam Mujtaba; Shah, Saeedah; Qadri, Naveed Ali (Annals of Human and Social Sciences, 2025)
This research aims to analyze fatalities caused by terrorism in Pakistan and assess the role of the National Action Plan (NAP) in countering terrorism and extremism. Terrorism has posed a severe threat to Pakistan’s security, integrity, and socio-economic development, placing the country at the forefront of the global fight against terrorism. Data was collected from secondary sources, and analyzed through content analysis. From 2001 to 2020, terrorism events were categorized into three phases: low casualties (2001-2006), intensified counter-terrorism operations (2007-2015), and reduced fatalities (2017-2020). In total, 15,397 incidents resulted in 20,636 civilian and 7,318 security personnel deaths, while 33,236 terrorists were eliminated. The National Action Plan, anti-terrorist financing measures, and strengthening NACTA were pivotal strategies. Addressing the root causes of extremism requires education reforms, economic development, stricter anti-terror financing controls, enhanced inter-agency coordination, and sustained implementation of counter-narrative campaigns. These measures are crucial for minimizing terrorism and fostering lasting peace.